The Effects of isomerization and vulcanisation temperature on the tear strength of natural rubber latex film - Samsuri Azemi (Journal of Rubber Research, 2005)
Natural rubber (NR) is predominantly (100;) cis 1,4 polyisoprene. As a consequence of its regular microstructure, vulcanised NR can undergo strain-crystallisation. In the case of NR latex film, strain-crystallisation promotes knotty tearing, a peculiar feature which is commonly observed in reinforcing black-filled NR vulcanisate but not in NR unfilled (gum) vulcanisate prepared from dry rubber. Knotty tearing enhances the tear strength of NR latex film, where its tearing energy can reach 100 kJm-2. The effects of isomerization, and temperature of vulcanisation on the tear strength of NR latex film were investigated. Isomerisation of NR latex disturbs the regularity of the microstructure and thus inhibits strain-crystallisation. In the absence of strain-crystallisation, NR latex film did not produce knotty tearing. Consequently its tearing energy was relatively low (1.0 kJm-2 - 12 kJm-2) depending on the speed of the test. The tearing energy of NR latex film was also found to decrease as the temperature of vulcanisation was increased which might be attributed to lower concentration of polysulphidic type of crosslinks at high vulcanisation temperature than that produced at low temperature vulcanisation.
Keywords: Black-filled; Energy; Isomerization; Latex film; MIcrostructure; Natural Rubber; Strain-crystallisation; Strength; TEar; Tempearature; Unfilled; Vulcanisate